ZISWAF FUND MANAGEMENT MODEL (ZAKAT, INFAK, SEDEKAH, AND WAKAF) IN PEOPLE'S ECONOMIC INSTITUTIONS - Ervan Irham Herdian (Nurul Jadid University, 2025)
Management of Zakat, Infaq, Alms and Waqf (ZISWAF) funds is one of the Islamic financial instruments that has great potential to reduce poverty levels and support community economic empowerment. This research discusses the ZISWAF fund management model which is based on the principles of transparency, accountability and digital innovation to increase efficiency and public trust. By integrating technology such as blockchain, big data analytics, and sharia-based crowdfunding applications, ZISWAF fund management can be maximized to support MSME development, educational programs, and job skills training. This research also identified various challenges, such as low public literacy, limited regulations, and lack of coordination between institutions. The proposed solutions include strengthening regulations, developing digital infrastructure, and collaborating with stakeholders. The research results show that a strategic and integrated approach in managing ZISWAF funds is able to produce sustainable socio-economic impacts while increasing the community's economic independence.